Effect of thermal treatment on the agronomic efficiency of nepheline sienite - Siqueira, José Oswaldo; Guedes, Geraldo A. A. (Pesquisa Agropecuaria Brasileira, 2014)
The effect of thermal treatment on the fertilizer value of nepheline sienite (NS) was evaluated. Heating NS alone at temperatures ranging from 110 to 900 °C during one hour had no effect on the amount of soluble K, as evaluated by chemical analysis and biological extraction using com (Zea mays, L.) plants. However, mixtures composed of NS + limestone heated at 900 and 1.150°C increased K solubilization by 50% as evidenced by chemical analysis. Mixture calcination of 1/2 SN + + 112 dolomitic lime resulted in material with fertilizing and liming properties with 3-4% of K2O, 18-20% of CaO and 10-12% of MgO. This mixture exhibited agronomic efficiency as good as KCI and had calcium carbonate equivalent neutralizing value between 60 to 70%. It is evidenced that NS, a potassium rock with low solubility, can be transformed into a corrective fertilizer with desirable characteristics to low-fertility acid soils, that predominates in Central Brazil, where deposits of K soluble salts are not known.
Keywords: potassium rock; calcination; potassium fertilizer